Adverse events following immunization against SARS-CoV-2 (covid-19) in the state of Minas Gerais - Silva, Roberta Barros da; Silva, Thales Philipe Rodrigues da; Sato, Ana Paula Sayuri; Lana, Francisco Carlos Felix; Gusmão, Josianne Dias; Souza, Janaina Fonseca Almeida; Matozinhos, Fernanda Penido (Revista de Saúde Pública, 2021)
OBJECTIVE To analyze adverse events following immunization (AEFI) against SARS-CoV-2 (covid-19) in the state of Minas Gerais (MG), Brazil. METHODS Epidemiological, descriptive study, with data from e-SUS Notifica (e-SUS Notification) in the state of Minas Gerais from January 20 to March 5, 2021. All suspected cases of AEFI of the covid-19 vaccine in the state were analyzed, totaling 7,305 cases. In this study, we verified the possible correlation between AEFI and the possible immunobiological administered causalities. The variables analyzed for AEFI cases were the immunobiological agent administered (AstraZeneca or Coronavac), the type of event, the evolution of the case, and the time in days since the administration of the immunobiological agent and the onset of symptoms and causality. The incidence rate (IT) was calculated for 100,000 doses applied. RESULTS The occurrence of AEFI as a result of the covid-19 vaccine was frequent (TI: 777.12) in the state. However, only 3% were classified as a severe AEFI, with a 20.85 IT, and 4.71% of them evolved to deaths (8.19 deaths per 100,000 doses applied). Among the deaths analyzed, 84.4% were classified as preexisting conditions caused by factors other than vaccines. Regarding non-serious AEFI, 1.11% occurred by immunization errors (TI: 8.62 EI for every 100 thousand doses applied). CONCLUSION This work encourages the discussion about the importance of recording AEFI related to covid-19 vaccines, demonstrating its safety for the population.